2021
DOI: 10.3390/v13071234
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Squamous Cell Carcinoma Treatment in the Era of Immune Checkpoint Inhibitors

Abstract: While head and neck squamous cell carcinomas (HNSCC) are marginally decreasing due to the reduction in exposure to the major risk factors, tobacco and alcohol, the incidence of high-risk human papillomavirus (HPV)-positive oropharynx squamous cell carcinomas (OPSCC), especially those in the tonsil and base of tongue subsites, are increasing. Patients with the latter are younger, display a longer overall survival, and show a lower recurrence rate after standard-of-care treatment than those with HPV-negative OPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 136 publications
(200 reference statements)
0
10
0
Order By: Relevance
“…Thus, the impression is that the expression of PD-1/PD-L1 axis may be the reflection of the antitumor reactivity rather than a sign of immune exhaustion. Recent studies have indicated that evaluation of PD-L1 protein status could assist in the selection of patients with OPSCC who are candidates for ICI immunotherapy ( 52 ). However, the role of ICI in platinum-refractory recurrent/metastatic (R/M) HNSCC is still controversial with only a small fraction of patients experiencing clinical benefit from anti-PD-1 monotherapy or in combination with chemotherapy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the impression is that the expression of PD-1/PD-L1 axis may be the reflection of the antitumor reactivity rather than a sign of immune exhaustion. Recent studies have indicated that evaluation of PD-L1 protein status could assist in the selection of patients with OPSCC who are candidates for ICI immunotherapy ( 52 ). However, the role of ICI in platinum-refractory recurrent/metastatic (R/M) HNSCC is still controversial with only a small fraction of patients experiencing clinical benefit from anti-PD-1 monotherapy or in combination with chemotherapy ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…The same can be said about the GORTEC 2015-01 PembroRad trial, which failed to improve locoregional control over SOC using pembrolizumab plus radiation (125). However, these are just two of the many ongoing trials involving LA HNSCC (118)(119)(120)(121)(122)(123). More importantly, some recent trials, albeit fewer in comparison, are now evaluating ICIs combinations specifically in LA, HPV + OPSCC with and without reductions in the dosage of radiation (Table 1).…”
Section: Targeting the Tumor Microenvironment Of Hpv +-Hnsccmentioning
confidence: 98%
“…Harnessing the positive effects of radio-and chemotherapy can therefore increase the proportion of responders and amplitude of response to ICIs and help with de-escalation endeavors. To that end, a number of clinical trials have incorporated ICIs in combination with radiation, chemotherapy or experimental targeted therapies for evaluation in LA HNSCC (118)(119)(120)(121)(122)(123).…”
Section: Targeting the Tumor Microenvironment Of Hpv +-Hnsccmentioning
confidence: 99%
“…Recently, more efforts have also been made to disclose their effects in the head and neck region. This Special Issue on "HPV in the head and neck region" includes, one editorial, eight reviews, one brief report and two systematic reviews that contribute to the overall knowledge of HPV in the head and neck region [1][2][3][4][5][6][7][8][9][10][11][12].…”
mentioning
confidence: 99%
“…Striving towards improved treatment options of OPSCC in the era of check point inhibitors was also covered and this review suggests that indeed new options for the future will fuel the next evolution of treatment for OPSCC [7]. Additionally, regarding treatment, a review is included on the relevance of HPV in head and neck cancer and what remains in 2021 from a clinician's point of view [8].…”
mentioning
confidence: 99%